Hierarchical Porous Carbon Cathode for Lithium–Sulfur Batteries Using Carbon Derived from Hybrid Materials Synthesized by Twin Polymerization. (31st October 2018) - Choudhury, Soumyadip; Ebert, Thomas; Windberg, Tina; Seifert, Andreas; Göbel, Michael; Simon, Frank; Formanek, Petr; Stamm, Manfred; Spange, Stefan; Ionov, Leonid
Abstract: A new route of fabrication of cathodes for lithium–sulfur (Li–S) batteries with high cycle stability is reported. The cathodes are fabricated using porous carbon materials obtained from hybrid materials synthesized by twin polymerization on sulfonated polystyrene microparticles. The sulfonic acid groups act as room temperature catalyst for twin polymerization resulting in the formation of nanostructured phenolic resin/silica hybrid materials on the surface of sulfonated polystyrene particles. The shell formed by phenolic resin is transformed into carbon by simple pyrolysis and the polystyrene core is decomposed simultaneously at the pyrolysis temperature yielding porous carbon/silica nanocomposite hollow spheres. After silica removal, a hierarchical, highly porous carbon is obtained. Melt mixing of the carbon with sulfur is used for the fabrication of cathodes for Li–S batteries. The presence of silica on one hand imposes strength to the sphere wall during the carbonization and depolymerization of polystyrene, and on the other hand generates microporous carbon material for lithium–sulfur batteries. The nanostructured hybrid cathode allows very high capacity of 800–1000 mAh gsulfur −1 and remarkable reversible cycling stability and rate capability over 200 cycles at 0.1C rate and over 440 cycles at 1C rate for Li–S batteries. Abstract : Twin polymerization is performed on self‐catalyzing sulfonated polystyrene colloidal crystal arrays for producing carbon substrate for sulfur . This twin monomer upon polymerization and carbonization leads to the formation of hierarchical porous carbon‐silica hybrid functional material, which results in hierarchical porous carbon. After sulfur filling into the pores by melting, the cathodes show remarkable cycle stability and rate performance.